2014
DOI: 10.1097/md.0000000000000152
|View full text |Cite
|
Sign up to set email alerts
|

Association of the Charlson Comorbidity Index with Renal Outcome and All-Cause Mortality in Antineutrophil Cytoplasmatic Antibody-Associated Vasculitis

Abstract: The aim of this study is to determine the effect of comorbidity assessed by the Charlson comorbidity index (CCI) at the time of diagnosis on the outcome of antineutrophil cytoplasmatic antibody (ANCA) associated vasculitis (AAV).This is a longitudinal observational study of 30 consecutive patients with AAV who were diagnosed and followed from January 1996 to December 2011. The degree of comorbidity at diagnosis and last visit was scored according to the age-adjusted Charlson comorbidity index (CCI (a)). The po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Our results also suggest that other patient-specific factors (such as the baseline ECOG Performance Status and the CCI) contribute to reduced tolerance of immunosuppression. Some previous studies have also found that comorbidity is correlated with lower patient and renal survival rates [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 96%
“…Our results also suggest that other patient-specific factors (such as the baseline ECOG Performance Status and the CCI) contribute to reduced tolerance of immunosuppression. Some previous studies have also found that comorbidity is correlated with lower patient and renal survival rates [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 96%
“…Based on the guideline of prevention and treatment of hypertension in primary care, primary care providers must carry out family visit at least once every 3 months, so the frequency of family visit was set as dichotomous variable with the option of less than 4 times per year or more. Patients’ comorbidities were tested by Charlson comorbidity index [32], which was broadly used in experimental and clinical researches.…”
Section: Methodsmentioning
confidence: 99%
“…11 Chronic kidney disease was based upon an estimated glomerular filtration rate of <60 ml/min/1.73 m 2 . 12 Drugresistant organisms included methicillin-resistant Staphylococcus aureus and penicillinresistant streptococci. The study was approved by the Trust's clinical effectiveness unit.…”
Section: Data Collectionmentioning
confidence: 99%